Analysis of Quality and Phenolic Metabolome of Thompson Seedless Raisins from Nine Production Areas in Turpan - HU Jinge, BAI Shijian (Shipin Kexue)
The differences in the quality and antioxidant activity of Thompson seedless raisins from nine production areas in Turpan were analyzed. Their phenolic composition and content were determined by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The results showed that raisins produced in Lianmuqin had the largest mean single unit mass and shape index of 0.81 g and 2.74, respectively, while raisins produced in Gaochang had the smallest values of 0.46 g and 2.27, respectively. Raisins produced in Yuanyichang had the highest solid/acid ratio of 29.34, while raisins produced in Qiketai had the lowest value of 25.74. Lianmuqin raisins had the lowest a* value of 2.56 and a ΔE value (44.94) below the medium level, indicating the greenest color. The a* value of Yuanyichang raisins was below the medium level (2.94) and its ΔE value (44.19) was the lowest. The color of raisins from these two areas tended to be green and the most consistent with each other. A total of 518 monomeric phenolics were identified in Thompson seedless raisins from the six production areas, including 275 flavonoids (53.09%), 136 phenolic acids (26.25%), 60 lignans and coumarins (11.58%), 19 tannin (3.67%) and 28 others (5.41%). A total of 246 differential metabolites were identified in raisins from Lukeqin versus Gaochangqu (124), Qiketai versus Shengjinxiang (144), and Yuanyichang versus Lianmuqin (66), with 54, 92 and 22 differential metabolites being unique to these comparisons, respectively and 10 differential metabolites being common to all of them. The above results indicate that Lianmuqin and Yuanyichang can be considered as advantageous production areas for Thompson seedless raisins.